Fostering Self-Regulated Learning with H5P Technology: The Pedagogical Experiences of Educational Professionals - Kerr, Ashford (International Journal of E-Learning & Distance Education / Revue internationale de l’apprentissage en ligne et de l’enseignement à distance)

(untitled) (AU Press, 2025)
This qualitative study examined the perspectives of educational professionals on integrating H5P technology to foster self-regulated learning (SRL) in blended learning environments at a post-secondary institution in Ontario, Canada. Using a phenomenological approach, data were collected through semi-structured interviews with five educators, five instructional designers, and five educational technologists, and analyzed thematically through the lens of Zimmerman’s SRL framework. The findings highlight key challenges in fostering learners' motivational processes (e.g., self-efficacy and autonomy), metacognitive processes (e.g., monitoring and planning), and behavioural processes (e.g., strategy execution) within blended contexts. The study evaluated the pedagogical applications, limitations, and potential of various H5P tools, such as interactive books, branching scenarios, and drag-and-drop activities, in supporting SRL. While advancements in H5P functionalities were noted, significant gaps were identified in aligning the technology with SRL best practices. These insights contribute to bridging gaps in literature and practice by offering actionable recommendations for optimizing H5P to enhance learners' SRL strategies. This research provides valuable implications for educators, instructional designers, and policymakers, laying the groundwork for future studies on leveraging educational technologies to support SRL in blended learning environments.